Incidental bycatch mortality and fishing restrictions: impacts on juvenile survival in the Endangered Saimaa ringed seal Pusa hispida saimensis - Jounela, Pekka; Sipilä, Tero; Koskela, Jouni; Tiilikainen, Raisa; Auttila, Miina; Niemi, Marja; Kunnasranta, Mervi
2019